Fiber Formation from Silk Fibroin Using Pressurized Gyration. Issue 1 (22nd November 2018) - Heseltine, Phoebe Louiseanne; Hosken, Joseph; Agboh, Chris; Farrar, David; Homer‐Vanniasinkam, Shervanthi; Edirisinghe, Mohan
Abstract: Silk has attracted considerable interest for use in biomedical applications due to its high strength and promising biocompatibility. Degummed silk, consisting only of silk fibroin (SF), has been processed using various methods and can be made into films, sponges, and fibers. Pressurized gyration (PG) is capable of rapidly producing aligned fibers and offers a great amount of control over their structure and morphology. Here, SF fibers are produced for the first time using PG. The effect of varying SF concentration and applied working pressure to the gyration vessel is reported, along with the resulting effect on fiber diameter, morphology, and structural composition. Aligned microfibers are found at concentrations of 8, 10, 12 w/v%, with the lowest fiber diameters reported at 8 w/v% SF 0.3 MPa applied pressure (2.1 ± 1.3 µm). Fourier‐transform infrared spectroscopy (FTIR) confirms the existence of PG spun fibers in both random coil and β‐sheet formations. Abstract : Pressurized gyration produces aligned fibers with good control over structure and morphology . Silk fibroin fibers are produced for the first time using pressurized gyration. The effect of varying polymer concentration and applied working pressure in the gyration vessel on the output fiber diameter, and morphology is reported. Silk fibroin exists in the fibers in random coil and β‐sheet conformations.